Religious Education in Europe in the Intercultural Era - Mirosław Wierzbicki (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article undertakes an analysis of various aspects of religious education in Europe in the intercultural and interreligious era. In particular, it emphasizes education and its proposals from the Council of European Bishops' Conferences. The author presents international organisms, affecting religious education focusing, in particular, on the role of UNESCO and the Council of Europe. Document entitled "White Paper" offers substantial help to intercultural dialogue in European countries. The article, presents also the criteria for intercultural dialogue and civic education.